The employment quota and the effective labor insertion of people with disabilities: the impact on Peruvian labor market - Carbajal Gastelo, Paola (2020)
The discrimination that suffer people with disabilities is seen reflected in diverse aspects; being the acces to a job, the most vulnerable. That is the reason why the Peruvian government has stablished a percentage for the hiring of these community in the public sector (5%) and the private sector (3%) in order to provide them greater participation in the formal labour market and improve their life quality.The present article is based on an investigation about the employment quota system and its impact on the Peruvian labour market for people with disabilities. Based on the normative context, statistical information and compared experience, the author proposes mesures that can be implemented in the interests of greater labour insertion.